Analisis Debit Banjir Rancangan Dan Kapasitas Tampang Sungai Di Sekitar Kawasan Sempadan Sungai Sokong Kabupaten Lombok Utara: Analysis Of Design Flood Discharge And River Case Capacity Around The Sokong River Border Area, North Lombok Regency - Ari Ramadhan Hidayat; Agustini Ernawati; Muhammad Khalis Ilmi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
In line with the North Lombok Regency (KLU) government program to prioritize handling and structuring residential areas and disaster-prone areas in the Pemenang-Tanjung sub-district in 2022, it is necessary to carry out several technical studies to support the program. One of the technical studies that can be carried out is an analysis of the design flood and river capacity around the Sokong River section in Tanjung Village, which is a location that is classified as densely populated, with slums and residential areas close to the river border. This study aimed to determine the magnitude of the design flood discharge and the cross-sectional capacity of the Sokong river section. The method used in this study is a hydrological analysis using the Nakayasu Synthetic Unit Hydrograph method to determine the amount of design flood discharge for the 25-year return period (Q25th) and analysis of river cross-sectional capacity using Hec-RAS 4.1.0 software. The results of the analysis show that the Q25th that occurs along the Sokong River section is 131.32 m3/s and the simulation results use Hec-RAS 4.1.0 software. shows that the capacity of the Sokong River segment cannot accommodate the Q25th. Therefore, it is necessary to plan the arrangement of residential buildings around the border area of ​​the Sokong River by raising the elevation of the building to be free from flood inundation.